An ethnographic research on the commercialization of the town of Baler, Aurora - GIO ANGELO B. ESCANILLAS (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: The purpose of this ethnographic study was to investigate how resorts and other tourist attractions have changed life in Baler, Aurora.Method: The effects of this "progress" on the participants were monitored to determine their nature. We also conducted in-depth interviews with locals, during which we inquired about their length of residence in the area, their means of subsistence, and the impact of these businesses on their neighborhoods. Twenty residents of Bacong and Castillo Barangays answered the questionnaire.Findings: The data showed that there was a convergence of positive and negative impacts as the number of businesses increased, but the positives carried more weight.Implications/Novel Contribution: The Baler is the subject of this study’s in-depth analysis. The findings will provide helpful information for tourism policymakers. These findings are also useful for vacationers on the lookout for new destinations. They’ll have a better time in general if they take a trip to the city.